2017
DOI: 10.15694/mep.2017.000012
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Knowledge regarding Surgical Treatment of Obesity among Final Year Medical Students and Recent Graduate Physicians from King Abdulaziz University

Abstract: Aim: To determine level of knowledge of medical students and recent graduates' physicians regarding the possibility of surgical treatment for obesity. Background:Over the last few decades, the development of bariatric surgery has been observed. Which represents currently the only permanent and comprehensive method for the treatment of obese patients. However, knowledge about the possibility of surgical procedures among general practitioners is not sufficient. That might be due to lack of knowledge about bariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…They accounted, 41% and 64.8% of the patients who have heard about the indications and complications of sleeve gastrectomy. Another study conducted in Jeddah, Saudi Arabia [18], indicated that among 298 medical students, 73% and 78.9% of them were able to distinguish the correct indications and complications of bariatric surgery which were slightly higher than our report. Although, it is expected that the knowledge of medical students is better than the general population.…”
Section: Discussioncontrasting
confidence: 79%
“…They accounted, 41% and 64.8% of the patients who have heard about the indications and complications of sleeve gastrectomy. Another study conducted in Jeddah, Saudi Arabia [18], indicated that among 298 medical students, 73% and 78.9% of them were able to distinguish the correct indications and complications of bariatric surgery which were slightly higher than our report. Although, it is expected that the knowledge of medical students is better than the general population.…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, in a study done targeting final year medical students in Jeddah, Saudi Arabia which tested their knowledge regarding obesity and bariatric surgeries found that they have a low level of knowledge. [23]…”
Section: Discussionmentioning
confidence: 99%
“…[2] In Saudi Arabia, there has been a very rapid increase in obesity rate according to a recently published report that estimated that approximately 75% of Saudi adults are overweight; this is thought to be the highest rate worldwide and has been attributed mainly to diet and sedentary life style. [3] Excess weight increases the risk of many disorders that are associated with high morbidity and mortality, such as type 2 diabetes, high blood cholesterol, hypertension, and coronary heart disease (CHD). It has also been associated with osteoarthritis, gall bladder disease, sleep disorders, non-alcoholic fatty liver disease and certain malignancies.…”
Section: Introductionmentioning
confidence: 99%